Protocols for fungicide sensitivity assay using detached leaf and DNA extraction for Phytophthora infestans - Guha Roy, S.; Dey, T. (2025)
This protocol manual provides standardized methods for assessing fungicide sensitivity in Phytophthora infestans using detached leaf assays and DNA extraction techniques. Developed for use in Asiablight training and regional surveillance, the protocols enable laboratories to generate comparable baseline sensitivity data and monitor changes in fungicide efficacy over time. By supporting evidence-based disease management, the document contributes to improved late blight control, reduced fungicide misuse, and enhanced resilience of potato production systems.